Cross-national comparative perspectives from the world internet project - Cardoso, G.; Liang, G.; Lapa, T. (The oxford handbook of internet studies, 2013)
This chapter reviews the diffusion, uses, and impacts of the Internet worldwide and over time. The World Internet Project has been intended to become the vehicle for tracking what happens as households and nations adopt and use the Internet. The study of the connection between the Internet and society presents a window onto contemporary societies. The Internet mediates social changes and social relations. The age of users, the institutional context, and media culture determine the Internet use in a given country. The Internet has been more of a complement to the traditional media than a competitor, and displacement effects are hard to find and are not general or universal across countries. It is important to keep a vital perspective in comparative approaches, being mindful of the theory that differences verified between countries or continenta can lose much of their analytical relevance.